PERANCANGAN SISTEM INFORMASI INDEKS PENYAKIT RAWAT INAP MENGGUNAKAN MICROSOFT VISUAL STUDIO 2010 - Citra Halidia Ramadhani; Yuda Syahidin; Lathifah Umarul Ridiyat; Leni Herfiyanti (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
This research the medical record activities which has an influence on the quality medical services in hospitals are data processing, especially in making disease indexes and actions. The disease index activity found in this study is the processing of inpatient disease index data that has been computerized and integrated at SIMRS, but inputting disease index data is still done by pulling patient disease diagnosis data one by one into Microsoft Excel from SIMRS. So that the data input takes a long time and the patient's disease index cannot be processed as a whole into a report. This research aims to produce design of a disease index information system for inpatients using Microsoft Visual Studio 2010 and interviews were conducted directly by researchers to officers as a research method, observation and equipped with a literature review. The result of this study is to develop an existing patient disease index information system into an integrated information system so that the preparation of patient disease index reports can be done quickly, precisely and accurately.